Sulfate is incorporated into cysteine to trigger ABA production and stomata closure - Batool, Sundas; Uslu, Veli Vural; Rajab, Hala; Ahmad, Nisar; Waadt, Rainer; Hell, Rüdiger; Wirtz, Markus (The plant cell, 2018)
Recent studies have demonstrated that soil-drying induces root-to-shoot sulfate transport via the xylem and that sulfate closes stomata. Here we provide evidence for a physiologically relevant signaling pathway that underlies sulfate-induced stomata closure.
Aktuelle Artikelversion am 28.01.2019 veröffentlicht
Gesehen am 06.02.2019